Evaluation of changes in tongue pressure with twin-block appliance therapy in growing Class II Div 1 malocclusion. An in vivo study - Sandhya Maheshwari; Arbab Anjum; Grateful S Suting; Saherish Farhan; Abid A Khan (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: Twin-block appliance therapy in patients with Class II Div 1 malocclusion positions the mandible anteroinferior leading to possible alterations in tongue pressure, tongue length, and the oropharynx. OBJECTIVES: To evaluate the changes in tongue pressure, tongue length and dimension of the pharyngeal airway in Class II Division 1 subjects before and after twin-block therapy. MATERIALS AND METHODS: Twenty-four subjects were selected, in the range of 10-14 years (mean-12 years). The tongue pressure was recorded at three regions with sensors placed at the incisive papilla and bilaterally at the molar region of the palate for four minutes. The root mean square (RMS) values were recorded and used for further analysis. Evaluation of tongue length and pharyngeal airway dimension was done using a lateral cephalogram. All the measurements were done before and after twin-block appliance therapy. The paired t-test was performed to compare the changes. RESULTS: Resting tongue pressures decreased from pre-treatment levels to post-treatment at all three regions. Change in ANB angle was found to have a significant negative correlation with tongue length, and pharyngeal airway dimension, a significant positive correlation with pressure at incisive papilla and left molar region and no correlation at right molar region. CONCLUSION: There was a decrease in resting tongue pressure as the malocclusion was corrected from Class II to Class I. Hence, this decrease in pressure could be a contributory factor in the maintenance of the dental equilibrium as lighter forces exist in the oral cavity.